Melon Fly, Bactrocera cucurbitae Coquillett (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; John B. Heppner; Thomas R. Fasulo (EDIS)
Within its range, the melon fly, Bactrocera cucurbitae Coquillett, is one of the most important pests with which vegetable growers have to contend. Although found in Hawaii, it is not present in the continental United States. This document is EENY-199 (originally published as DPI Entomology Circulars 29 and 315), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001. Revised: July, 2004.